PEMBERDAYAAN MASYARAKAT MELALUI BADAN USAHA MILIK DESA “NGINGAS MAKMUR ABADI” DESA NGINGAS KECAMATAN WARU KABUPATEN SIDOARJO - Bariq Rakhmadian; Lukman Arif (Halu Oleo University, 2023)
Village community empowerment is carried out to develop independence and improve community welfare by increasing skills and abilities in managing and utilizing existing resources. This study aims to analyze and describe the process of Community Empowerment through Village-Owned Enterprises